Cultural identification of the upper Ob population of the early iron age based on the materials of archaeology and anthropology (Bystrov necropolis) - Borodovskiy Andrey P. (Поволжская археология)
The article is devoted to the analysis of the interpretation of the cultural affiliation of the population in modern anthropological publications of the materials of the big necropolis, located in the Iskitims district of Novosibirsk region (Bystrovka-1,2,3). The duration and comprehesivity (archaeological, anthropological and natural science research) of the study of this archaeological heritage site allows us to consider it as a standard monument on the ancient history of the Upper Ob population of the Early Iron Age. The complex organization of the necrosphere of the Bystrovka necropolis, the relative duration of functioning and multiculturalism of burial rites (of the population of the Berezovsky historical stage of the Early Iron Age of the Upper Ob, as well as representatives of the Kulai and Sargat cultural traditions) allow us to consider in detail the issues of correlation in the format of archaeological culture and anthropological attribution.